CHARACTERISTICS OF PATIENTS WITH TYPE 1 DM AND LADA IN A MALAYSIAN PUBLIC HOSPITAL - Ci, Goh Qing; Yee Yee, Yoh; Nee, Low Yen; Voon, Tong Chin (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Type 1 diabetes mellitus (DM) occurs as the result of pancreatic beta cell destruction. Latent autoimmune diabetes in adults (LADA) is immunologically similar to T1DM but immune destruction progresses at a slower rate. The aim of the study is to identify the clinical characteristics of patients with T1DM and LADA in our clinic. METHODOLOGY This is a single centre cross-sectional study involving all 122 patients with T1DM and LADA. Information was obtained from patients’ records and interviews during follow up. RESULTS There were 49 males (40.2%) and 73 females (59.8%) with a mean age of 35.3 (SD 14.9) years old. The mean duration of disease is 12.9 (SD 9.7) years. Ninety-five subjects (77.9%) have T1DM and 27 subjects (22.1%) have LADA. The most common complication was retinopathy (14.8%). Almost 2/3 of subjects (61.5%) reported having minor hypoglycemia and 15 (12.3%) had diabetic ketoacidosis in the past year. The most common co-morbid is dyslipidemia (45.9%). Eighteen percent of the subjects have other autoimmune diseases. Majority of the subjects were on at least one analogue insulin (93.4%) and on basal bolus regimen (89.3%). Only 6 subjects (4.9%) were on insulin pump. One hundred fourteen (93.4%) subjects performed self-monitoring of blood glucose (SMBG) and only 26 (21.3%) subjects have used continuous glucose monitoring systems (CGMS) at least once. The mean HbA1c is 8.91% (SD 2.2). The most frequent pancreatic autoantibodies detected were glutamic acid decarboxylase (GAD) (77.9%) and islet cell antibody (ICA) (77.7%). CONCLUSION Majority of our subjects with T1DM and LADA are on analogue insulin andon basal-bolus regimen with most of them performing SMBG. Despite this, the rate of hypoglycemia is high and control remains suboptimal. Increasing the use of technologies such as CGMS and insulin pumps which are not fully utilized at present, may improve outcomes.